Caribbean economies 2006 : a preliminary overview - Buitelaar, Rudolf (ECLAC Port of SpainTT, 2007)
Provides a general regional overview of Caribbean economies in 2006, based on preliminary data and focused on the CARICOM economies, with the exception of Haiti. Contains individual country briefs.